Poor CD4 recovery and risk of subsequent progression to AIDS or death despite viral suppression in a South African cohort. Issue 2 (3rd March 2014) - Takuva, Simbarashe; Maskew, Mhairi; Brennan, Alana T; Long, Lawrence; Sanne, Ian; Fox, Matthew P
Abstract : Introduction: The prognostic role of CD4 response in the first six months of treatment in patients achieving early viral suppression during HIV treatment is unclear. Methods: This was a cohort study of HIV‐positive adults initiating antiretroviral therapy (ART) between April 2004 and August 2007 who achieved viral suppression (<400 copies/ml) by six months on treatment in South Africa. Immunological response at six months was defined as: (1) absolute CD4 reached (<200 vs. ≥200 cells/ml); (2) absolute CD4 reached (0–49, 50–200 and ≥200 cells/ml); and (3) CD4 increase from ART initiation (<0, 0–49, 50–199 and ≥200 cells/ml). We used Cox regression models to determine the relationship between each definition and both new AIDS‐defining condition and death. Results: A total of 4129 patients were eligible for analysis; 212 (5.1%) of those patients experienced a new AIDS‐defining condition and 154 (3.7%) died. Smaller CD4 gains by six months were associated with higher hazards of progression to AIDS (CD4<50 vs. ≥200 cells/ml; adjusted hazard ratio (aHR): 2.6; 95% CI: 1.2–2.1) and death (aHR: 2.8; 95% CI: 1.4–5.7). A decrease in CD4 count since ART initiation through six months (aHR: 2.4; 95% CI: 1.2–4.9) and smaller CD4 count gains (0–49 cells/ml; aHR: 2.0; 95% CI: 1.2–3.4 and 50–199 cells/ml; aHR: 1.5; 95% CI: 0.9–2.2) were also associated with greater risk of progression to AIDS compared to an increase of ≥200 cells/ml. When we examined mortality differences by gender among this virally suppressed cohort, a higher proportion of males died compared to females, 4.7% versus 3.2%, p= 0.01. However, in multivariable analysis, we did not observe any significant differences: aHR: 1.39; 95% CI: 0.98–1.95. Conclusions: Patients on ART with poor CD4 recovery early in treatment are at greater risk of progression to new AIDS diagnosis or death despite viral suppression. Approaches to managing this sub‐group of patients need further investigation.